Cyanobacteria Recent Advances and New Perspectives - Tiwari, Archana (IntechOpen, 2023)
Cyanobacteria are a unique class of microalgae that are not only valuable to the environment but also find uses in a wide variety of contexts, including agriculture, renewable energy sources, drug molecules, and various high-value compounds. The eight chapters of Cyanobacteria - Recent Advances and New Perspectives explore recent advances in diverse cyanobacteria topics: picocyanobacteria in surface water bodies, removal of microcystins from drinking water, applications of cyanobacteria for antioxidative enzymes, bioplastics, antimicrobial substances, nanoparticles, biofuels, and sustainable agriculture. The information in this book will be valuable to scientists, academicians, and scholars worldwide.